Interactive sequences between fathers and preterm infants in the neonatal intensive care unit. (January 2020) - Stefana, Alberto; Lavelli, Manuela; Rossi, Germano; Beebe, Beatrice
Abstract: Aims: The first purpose of the study was to examine fathers' spontaneous communicative behavior with their preterm infants in the neonatal intensive care unit, and how father's and infant's behaviors affected each other. The second purpose was to examine any possible association between the fathers' and/or infants' characteristics and the quality of fathers' behaviors with their infants. Study design/Subjects/Outcome measures: Father–preterm infant dyads (n=20) were assessed at 34-36 weeks postmenstrual age, during a spontaneous face-to-face communication with the infant placed in a heated cot in the NICU, and coded according to the Parent-Preterm Infant Coding System. Results: The presence of the father's Affiliative Behavior increased the occurrences of infant Gazing at the parent's face. In turn, infant gazing increased the occurrence of paternal Affiliative Behavior. The likelihood of infant's Gazing at the father's face was also significantly elicited by infrequent occurrences of paternal Affectionate Talk, co-occurring with Gazing at infant with Positive Facial Affect (but no Touch). With regard to the predictors of quality in father–infant interactions, we found a significant positive correlation between fathers' level of depressive symptomatology and fathers' Affiliative Behavior. Conclusion: Our results show the of bidirectional sequential patterns of communication between fathers and preterm infants at 35 weeks postmenstrual age, and provide important information about the quality and modalities of paternal communication and their influence on infant behavioral states. From a clinical perspective, these results suggest that father-specific interventions designed to improve and sustain fathers' positive engagement with infants in the NICU should be pursued. Highlights: Father–preterm infant bidirectional interactive sequences are present at 35 weeks PMA. Paternal vocalizations play a central role in evoking the infant's gaze. Paternal touch can help the preterms attain and maintain a calm state.